Debt Brakes in the German States: Governments' Rhetoric and Actions - Niklas Potrafke; Marina Riem; Christoph Schinke (Center for Economic Studies and ifo Institute (CESifo), 2016)
In 2009 a new law on German debt brakes was passed: state governments are not allowed to run structural deficits after 2020. Consolidation strategies initiated today influence if a state can comply with the debt brake in 2020. We describe to what extent government ideology predicts if state governments consolidate budgets and which fiscal adjustment path they choose. Attitudes towards budget consolidation, as expressed by politicians' words in the public debate, differed among parties. Anecdotal evidence and descriptive statistics indicate that leftwing governments ran on average higher structural deficits than rightwing governments between 2010 and 2014. Primary deficits, however, hardly differed under leftwing and rightwing governments. Revenues of federal taxes were much higher than expected and facilitated budget consolidation. Leftwing governments did not need to run deficits to design generous budgets. It is conceivable that parties confirmed their identity by using expressive rhetoric, but responded to shifts in public opinion after the financial crisis and pursued more sustainable fiscal policies when in office.
Keywords: D72; H60; H72; 330; government ideology; public debt; debt brake; balanced-budget rule; constitution; expressive rhetoric